answersLogoWhite

0


Best Answer

x + 3y = 6

2x + y = -8

Solve by substitution:

x + 3y = 6 subtract 3y to both sides

x = 6 - 3y

2x + y = -8 substitute 6 - 3y for x

2(6 - 3y) + y = -8

12 - 6y + y = -8

12 - 5y = -8 subtract 12 to both sides

-5y = -20 divide by -5 to both sides

y = 4

x = 6 - 3y

x = 6 - 3(4) = 6 - 12

x = -6

Thus, the solution of the system is (-6, 4).

User Avatar

Wiki User

โˆ™ 2009-02-28 04:24:47
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1186 Reviews

Add your answer:

Earn +20 pts
Q: What is is X plus 3y equals 6 and 2x plus y equals -8?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked